Human Rights And Climate Change: Convergence From An International Perspective - Liyanage, I. (The Department of Law, Faculty of Arts, University of Jaffna / Surana and surana International Attorneys India, 2025)
Climate change poses serious challenges to various aspects of human life, including development, economic progress, and social advancement. According to the United Nations Environment Programme, climate change ranks among the most significant threats to human rights in our generation, endangering individuals’ and communities’ fundamental rights to food, health, life, and an adequate standard of living worldwide. Therefore, it is reasonable to identify climate change as a contemporary and rapidly emerging threat to the realization of human rights. However, the nexus between climate change and human rights remains ambiguous in many instances. At the international level, various initiatives have been undertaken to address these issues. Yet, significant unresolved aspects persist. Against this backdrop, the primary objective of this research is to analyse the convergence between the notion of human rights and the modern climate change regime. Secondly, this research aims to examine the measures taken by international environmental and human rights regimes to address this pressing issue. This study employs a desk research approach, focusing on key international instruments, United Nations resolutions, Human Rights Council reports, and jurisprudence in international environmental law. Furthermore, it considers contemporary developments in human rights jurisprudence to assess the scope and extent of the connection between human rights and climate change. The research suggests that the application of human rights obligations within the climate change regime faces significant limitations due to substantive and procedural barriers at the international level. In conclusion, this paper argues for the establishment of a robust institutional framework to hold stakeholders accountable for their human rights obligations in the context of climate change. Additionally, integrating core principles of international environmental law can provide a precise pathway toward the full realization of these rights in the contemporary world.
Keywords: Climate change; Human rights; International initiatives